005.4 Multiplex assay for simultaneous detection of mycoplasma genitalium and macrolide resistance using pass mnazyme QPCR. (13th September 2015) - Tabrizi, SN; Tan, LY; Walker, S; Poljak, M; Twin, J; Garland, SM; Bradshaw, CS; Fairley, CK; Mokany, E
Abstract : Introduction: Treatment of M. genitalium (Mg) infection with single dose 1 g macrolide antibiotic, azithromycin, is routinely utilised in clinical practice however this has been associated with emergence of macrolide resistance and ineffective cure rates. Mutations at two positions, 2058 and 2059 (E. coli numbering) in the Mg 23S rRNA gene have been associated with macrolide resistance. Simultaneous detection of Mg and mutations associated with azithromycin failure could be used to offer rapid delivery of effective second line regimens. This study evaluates a combined diagnostic-resistance assay for potential use in clinical settings. Methods: Clinical samples diagnosed with Mg were evaluated with a combined-diagnostic resistance assay that employs novel "Primer Assisted Sequence Switching" (PASS) primers coupled with Multi-component Nucleic Acid enzyme" (MNAzyme) detection. PASS primers selectively amplify target sequences resulting in enhanced specificity for mutant over wild-type and MNAzymes allow for efficient detection and discrimination of multiple mutations simultaneously. Multiplexed PASS MNAzyme qPCR was evaluated by comparison to previously screened clinical samples for Mg (MgPa gene) and 23S mutations using Sanger sequencing and HRM analysis. Results: Using artificial templates, this assay was able to detect mutation templates ranging from 10–10, 240 copies/reaction, with an associated Mg detection limit comparable to existing assays used in routine diagnostics. Preliminary screening of DNA from 24 clinical samples revealed Mg detection range of 3–300, 000 copies/reaction. This assay was able to detect the correct mutation in 21/24 cases (87.5%), however was not readily able to assign a mutation at the lowest concentrations tested, an issue present in all rapid mutation screening tests for Mg. Conclusion: Multiplexed PASS MNAzyme qPCR offers the ability for simultaneous detection of Mg and macrolide resistance mutations. This assay offers considerable advantages in clinical settings with rapid identification of macrolide resistant strains and the ability to implement effective second line agents without delay. Disclosure of interest statement: SpeeDx is the developer and manufacturer of the assay evaluated in this study.